2007
DOI: 10.1002/polb.21154
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal cold crystallization behavior and kinetics of polylactide/clay nanocomposites

Abstract: The nonisothermal cold crystallization behavior of intercalated polylactide (PLA)/clay nanocomposites (PLACNs) was studied using differential scanning calorimetry, polarized optical microscope, X-ray diffractometer, dynamic mechanical thermal analysis, and Fourier transform infrared spectrometer. The results show that both the cold crystallization temperature (T cc ) and melting point (T m ) of PLA matrix decreases monotonously with increasing of clay loadings, accompanied by the decreasing degree of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
138
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 68 publications
(137 reference statements)
41
138
1
Order By: Relevance
“…The values of fold surface energy σ e were obtained by solving Equation (11) and are listed in Table 3. For neat PLLA, the value of σ e varies in the range of 91-117 erg/cm 2 (1 erg/cm 2 = 1×10 -3 J/m 2 ), which agrees well with the result (107 erg/cm 2 ) by Miyata and Masuko (1998) but higher than 40.5 erg/cm 2 by Di Lorenzo (2001) and 43.5 erg/cm2 by Wu et al (2007). It has been shown that the value of σ e is dependent on the molecular weight of PLLA (Miyata and Masuko 1998) and the cooling or heating rate to the isothermal crystallization temperature (Wu, Wu et al 2007).…”
Section: Crystal Growth Analysis By Lauritzen-hoffman Theorysupporting
confidence: 81%
See 3 more Smart Citations
“…The values of fold surface energy σ e were obtained by solving Equation (11) and are listed in Table 3. For neat PLLA, the value of σ e varies in the range of 91-117 erg/cm 2 (1 erg/cm 2 = 1×10 -3 J/m 2 ), which agrees well with the result (107 erg/cm 2 ) by Miyata and Masuko (1998) but higher than 40.5 erg/cm 2 by Di Lorenzo (2001) and 43.5 erg/cm2 by Wu et al (2007). It has been shown that the value of σ e is dependent on the molecular weight of PLLA (Miyata and Masuko 1998) and the cooling or heating rate to the isothermal crystallization temperature (Wu, Wu et al 2007).…”
Section: Crystal Growth Analysis By Lauritzen-hoffman Theorysupporting
confidence: 81%
“…For neat PLLA, the value of σ e varies in the range of 91-117 erg/cm 2 (1 erg/cm 2 = 1×10 -3 J/m 2 ), which agrees well with the result (107 erg/cm 2 ) by Miyata and Masuko (1998) but higher than 40.5 erg/cm 2 by Di Lorenzo (2001) and 43.5 erg/cm2 by Wu et al (2007). It has been shown that the value of σ e is dependent on the molecular weight of PLLA (Miyata and Masuko 1998) and the cooling or heating rate to the isothermal crystallization temperature (Wu, Wu et al 2007). Miyata and Masuko (1998) implied that the value of σ e increases with increase in the loose-loop chains on the fold surface of high molecular weight PLLA.…”
Section: Crystal Growth Analysis By Lauritzen-hoffman Theorysupporting
confidence: 81%
See 2 more Smart Citations
“…There was a competition between fibre nucleating effect and hindrance of chain mobility, limiting the crystallite growth. This competition between the filler nucleating effect and its impeding effect on crystallization at high loading was also observed in PLA filled with clay by Wu et al (2007).…”
Section: Thermal and Thermo-mechanical Propertiesmentioning
confidence: 74%